Production Control Using the Kanban System in the Manufacturing Industry in Indonesia: Systematic Literature Review - Hibarkah Kurnia; Dwi Irwati; Sukron Makmudah; Irgi Sofani (DPPM Universitas Pelita Bangsa, 2023)
The existence of the manufacturing industry in Indonesia is heavily influenced by productivity so that it can compete with other countries. Productivity will not be achieved if the production process workflow does not have a manufacturing system. This is what causes requests from customers not to be fulfilled becausethere is a production process flow that still has problems with a shortage of raw materials or the quality is still below standard. This study aims to identify and analyze related to the design of work systems in the manufacturing industry in Indonesia so that customer needs can be met according to their requests. This study uses the Systematic Literature Review (SLR) method starting with journal collection, sorting journals according to topic, processing journals, and analyzing articles according to research topics. This study found several journals related to research topics based on a focus on 2016-2023. This research resulted in the year 2022 being the most published research with 5 articles, while based on the type of industry the most frequently found was the type of automotive industry with 6 articles or 30%. The theoretical implications of this research hope to add references for other researchers in their observations on the Kanban system. While realized in practice, this research serves as a guide in improving the production process flow using the Kanban system, to increase productivity in the manufacturing industry.